Validity of 5E-PBL Learning Cycle Model Based on TPACK to Improve Scientific Writing - Nisa, Khairun; Jamaluddin, Norliza; Santos, Joseline M. (International Journal of Language Pedagogy, 2025)
Scientific writing is a critical skill for students and educators, yet many continue to face substantial challenges in meeting academic writing standards. Studies reveal that only 14.25% of students are able to develop ideas supported by data analysis, while 66.67% struggle to express their thoughts in structured academic formats. Common difficulties include formulating and organizing ideas, using proper academic language, and referencing accurately. To address these issues, this study developed and validated the TPACK-based 5E-PBL Learning Cycle Model, aiming to enhance students’ scientific writing abilities. Employing the Plomp R&D model, the research proceeded through three phases: preliminary investigation, development and prototyping, and evaluation. Expert validation showed high content validity, with scores of 3.51 (88%) for model content, 3.52 (88%) for the model book, and 4.34 (87%) for the student guidebook. Implementation results indicate that the model effectively improves students' understanding of scientific writing structures, fosters critical thinking, and encourages meaningful integration of technology. This study concludes that the 5E-PBL Learning Cycle Model based on TPACK is a valid and feasible approach to address academic writing challenges. Further research is recommended to evaluate its broader impact across disciplines.